2018
DOI: 10.2147/ijn.s170148
|View full text |Cite
|
Sign up to set email alerts
|

Anti-EGFR-iRGD recombinant protein modified biomimetic nanoparticles loaded with gambogic acid to enhance targeting and antitumor ability in colorectal cancer treatment

Abstract: BackgroundRed blood cell membrane-coated nanoparticle (RBCm-NP) platform, which consist of natural RBCm and synthetic polymeric core, can extend circulation time in vivo with an improved biocompatibility and stability of this biomimetic nanocarrier. To achieve better bioavailability of antitumor drugs that were loaded in RBCm-NPs, the functionalization of coated RBCm with specific targeting ability is essential. Bispecific recombinant protein anti-EGFR-iRGD, containing both tumor penetrating peptide (internali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
48
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(49 citation statements)
references
References 68 publications
1
48
0
Order By: Relevance
“…Chemical synthesis is a common way to introduce targeting ligands to the surface of cell membrane, however, it may damage the property and protein components of the membrane, which the functions of cell membrane are based on. Based on this consideration, a lipid-insertion approach has been developed 26,35,56,57. Fu et al35 designed a DSPE-PEG (1,2-distearoyl-sn-glycero-3-phosphoethanolamine-PEG) decorated cyclic Arg-Gly-Asp (RGD), which could be simultaneously inserted into the phospholipid layer of erythrocyte membranes.…”
Section: Membrane Sources For Cmnpsmentioning
confidence: 99%
“…Chemical synthesis is a common way to introduce targeting ligands to the surface of cell membrane, however, it may damage the property and protein components of the membrane, which the functions of cell membrane are based on. Based on this consideration, a lipid-insertion approach has been developed 26,35,56,57. Fu et al35 designed a DSPE-PEG (1,2-distearoyl-sn-glycero-3-phosphoethanolamine-PEG) decorated cyclic Arg-Gly-Asp (RGD), which could be simultaneously inserted into the phospholipid layer of erythrocyte membranes.…”
Section: Membrane Sources For Cmnpsmentioning
confidence: 99%
“…As a result, the chemotherapy-induced ICD has been employed by previous studies to stimulate the immune response, which showed promising benefits in cancer therapy. 9 , 10 …”
Section: Introductionmentioning
confidence: 99%
“…In a similar way, RBC-NPs were modified by addition or recombinant anti-EGFR-iRGD to the NPs surface. This allowed these NPs to reach effective and exact cancer-targeting in a high EGFR-expressing colorectal cancer model, while NPs lacking peptide modification were less effective [71].…”
Section: Rbc Membrane-covered Npsmentioning
confidence: 99%